SIMULASI UJIAN PERSIAPAN TOEFL BERBASIS WEB DENGAN MENGGUNAKAN METODE INCREMENTAL PROCESS MODEL - Rudi Kurniawan (LPPM STMIK AMIK BANDUNG, 2022)
The Test of English as a Foreign Language (TOEFL) is an exam or test that measures a person's English ability. This test tests listening, structure, and reading skills. For STMIK